The first duck-billed dinosaur (Family Hadrosauridae) from Antarctica - Case, Judd A.; Martin, James E.; Chaney, Dan S.; Reguero, Marcelo Alfredo; Marenssi, Sergio Alfredo; Santillana, Sergio M.; Woodburne, Michael O.
Duck-billed dinosaurs or hadrosaurs are a very common family of dinosaurs in the Late Cretaceous of North America and Eurasia with rare occurrences in South America. Here, we report the first hadrosaur recovered in Antarctica from sandstones of late Maastrichtian age, Vega Island, Antarctic Peninsula (Fig. 1) during a joint U.S.-Argentinian geological and paleontological field expedition to the island. This discovery supports the hypothesis of a dispersal route between southern South America and Antarctica in the Maastrichtian. Fil: Case, Judd A. Saint Mary’s College of California; Estados Unidos Fil: Martin, James E. South Dakota School of Mines & Technology; Estados Unidos Fil: Chaney, Dan S. National Museum of Natural History; Estados Unidos Fil: Reguero, Marcelo Alfredo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Marenssi, Sergio Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Santillana, Sergio M. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Woodburne, Michael O. University of California; Estados Unidos